Pregnancy in a Methylmalonic Acidemia Patient With Kidney Transplantation: A Case Report. Issue 7 (24th May 2013) - Lubrano, R.; Bellelli, E.; Gentile, I.; Paoli, S.; Carducci, C.; Carducci, C.; Santagata, S.; Pérez, B.; Ugarte, M.; Labriola, D.; Elli, M.
Abstract Presently pregnancy is no more exceptional in women with metabolic diseases. However, it still poses significant medical problems both before and after childbirth. The challenge is even greater if the mother has undergone organ transplantation, because of her metabolic disease. We report on a case of pregnancy in a patient 29‐year‐old with methylmalonic acidemia cblA type (OMIM 251100) who received a renal transplantation at the age of 17 for end‐stage renal disease (ESRD) caused by her primary disease. During pregnancy neither metabolic crises nor renal function changes were observed in the mother, with the only exception of a mild increase of her systemic blood pressure. To the fetus pregnancy was uneventful and during the first 30 months after birth the baby's neuropsychomotor development was normal and there were no episodes of metabolic derangement. This is evidence that methylmalonicacidemia cblA, even when treated with renal transplantation for inherent ESRD, is no contraindication to pregnancy. It is even possible that a functioning transplanted kidney contributes to improve metabolic parameters.